Analysis of Applied Media in Public Service Advertisements “Tetap Fokus di Jalan” - Nenden Suryamanah Annisa; Hade Nadia Husnia; Zakarias Sukarya Soetedja (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Public service advertising is a government program that aims to educate the public on good values from the state's point of view. As the name implies, public service advertisements contain the word "advertisement" which means there is a "product" that is expected to be accepted and then consumed by the wider community. In public service advertisements, the advertised "products" are in the form of good values with the main goal of being able to benefit the government and the citizens themselves. In this study, the researcher will dissect a public service advertisement in the form of a video by using descriptive qualitative methods and using the aesthetic theory of applied media which is the scalpel. There are five aspects of research that become a reference for researchers in dissecting the work of this video advertisement, including: light and color, two-dimensional space, three-dimensional space, time/motion and sound. The results of this study indicate that the public service advertisement video "Tetap Fokus di Jalan" is successful in conveying the message in the form of a slick, interesting and creative video. From the five aspects of the research, this video advertisement is quite successful in presenting all five perfectly. So that it can support the plot of the story to be more dramatic. The packaging of this advertising video is sufficient to keep up with the times so that it can be accepted by young people who seem to be the main target of their audience